“I Learned How to Think, Not What to Think.” Student Perspectives on an Interdisciplinary Undergraduate Honours Programme - Jenny Godley; Lori Jane Pasaraba; Megan Wilson; Mabel Teye-Kau; Mark Migotti (Canadian Journal for the Scholarship of Teaching and Learning)
The Arts and Science Honours Academy (ASHA) is a unique interdisciplinary undergraduate honours programme at a large research-intensive university in Canada. Data were collected in early 2020 from 108 past and present students, representing the first eleven cohorts of the programme. Triangulating results from quantitative and qualitative analyses, we describe the ASHA students’ educational and social experience during their time at university and, for those who have graduated, their post-graduate activities. Situating our investigation within previous literature examining interdisciplinary undergraduate learning communities and high impact practices, we assess whether students from arts and science disciplines experienced the programme differently, and which aspects of the programme were most impactful. We find that academically, students reported benefiting from the exposure to interdisciplinary thought, the opportunity to do research, and the study abroad requirement. Socially, students reported benefiting from the connections they formed with a small cohort of high achieving peers from a variety of disciplinary backgrounds. While science students reported benefitting the most from ASHA socially, arts students were more likely to indicate that the programme influenced their careers following graduation. These findings provide evidence to support the creation and design of future interdisciplinary undergraduate programmes.